2005
DOI: 10.1126/science.1105833
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid Cation Formation and the Regulation of Photosynthetic Light Harvesting

Abstract: Photosynthetic light harvesting in excess light is regulated by a process known as feedback deexcitation. Femtosecond transient absorption measurements on thylakoid membranes show selective formation of a carotenoid radical cation upon excitation of chlorophyll under conditions of maximum, steady-state feedback deexcitation. Studies on transgenic Arabidopsis thaliana plants confirmed that this carotenoid radical cation formation is correlated with feedback deexcitation and requires the presence of zeaxanthin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
650
3
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 736 publications
(689 citation statements)
references
References 25 publications
25
650
3
3
Order By: Relevance
“…Recently, in thylakoid membranes under conditions of maximum, steadystate feedback deexcitation, upon Chl a excitation, a 11 ps rise component was observed at 1000 nm, in the region where one might expect to see a formation of a carotenoid radical. 39 The authors suggested that the rise is due to the formation of a charge-transfer state of a zeaxanthin-chlorophyll pair, which is then responsible for excess energy dissipation in thylakoid membranes in green plants. In principle, the protein environment will also affect the excited-state lifetime of chlorophylls; in most cases, it will shorten the lifetimes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in thylakoid membranes under conditions of maximum, steadystate feedback deexcitation, upon Chl a excitation, a 11 ps rise component was observed at 1000 nm, in the region where one might expect to see a formation of a carotenoid radical. 39 The authors suggested that the rise is due to the formation of a charge-transfer state of a zeaxanthin-chlorophyll pair, which is then responsible for excess energy dissipation in thylakoid membranes in green plants. In principle, the protein environment will also affect the excited-state lifetime of chlorophylls; in most cases, it will shorten the lifetimes.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 In previous work, the Zea radical cation (Zea •+ ) was observed in high-light-acclimated plant thylakoids using transient absorption (TA) spectroscopy. 6 However, these thylakoids had been high-light-acclimated for over 30 min before measurement, which does not indicate whether CT quenching is activated within the first few minutes of high light exposure, the time scale of qE activation. Zea •+ has also been observed in isolated minor (monomeric) light-harvesting complexes containing Zea, 11,12 but these protein conditions may not be indicative of in vivo behavior, and once again, do not give information about when CT quenching turns on during light acclimation.…”
Section: * S Supporting Informationmentioning
confidence: 92%
“…Light acclimation of the thylakoids, induced by continuous irradiation at 850 μmol photons·m −2 ·s −1 , leads to the formation of Zea •+ , resulting in additional rise (15.4 ps) and decay (40 ps) components ( Figure 1b). In a previous report, 6 the TA kinetic traces of the Zea •+ -depleted Arabidposis thaliana (npq4 mutant) indicated that the Chl excited-state absorption (ESA) signal is nearly identical in dark-and light-acclimated samples at 1000 nm. Therefore, Chl ESA dynamics and Chl*−Chl* annihilation were thought to contribute equally to the near-IR TA signals of dark-acclimated and high-light-acclimated thylakoids at the same Chl concentration and excitation laser intensity, and the observed difference kinetics directly indicate the population of the charge-separation states (Chl •− and Zea •+ ).…”
Section: * S Supporting Informationmentioning
confidence: 92%
See 1 more Smart Citation
“…Simultaneously, with PsbS protonation, de-epoxidized xanthophylls would also act as 'allosteric regulators' by amplifying the conformational changes within the whole LHC antenna. The physical process by which excitation energy is effectively converted into heat has only recently been understood (Holt et al 2005;Pascal et al 2005;Ruban et al 2007). The qE mechanism is rather similar in other organisms like the diatoms and the brown macroalgae given some peculiarities (see Chapter 7).…”
Section: Effect Of Light Stress On Fluorescence Signatures and Their mentioning
confidence: 99%